TRANSNATIONAL ṬARÎQA: The Expansion of Naqshbandī Haqqânî and the Fulfilment of Urban Spirituality - Asmarani, Dini; Monica, Sarah (Ulul Albab: Jurnal Studi Islam, 2023)
The following article examines the Naqshbandî Ḥaqqânî order as a spiritual oasis amidst urban life. This order has massively developed around the world, including in Indonesia through The Rumi Centre located in urban area. This ṭarîqa immerses followers in the philosophy of detachment from material possessions, which appeals to urban dwellers who live busy lives. The Naqshbandî Ḥaqqânî order's expansion is further supported by its simplified membership requirements and da’wah digitalization. This research using qualitative methods including participant observation, interviews, and literature studies to discover how The Rumi Center fulfills the spiritual needs of urban followers. The results show that this ṭarîqa successfully balances the lives of its followers through the daily practice of dzikr. Although the followers find solace and spiritual growth by detachment from material possessions, this philosophy may not resonate with every urban dweller. Their strong sufi tradition in their teachings do not resonate with all urban dwellers. The research's focus on urban areas imposes research’s limitations on those who are genuinely seeking alternative religious outside of mainstream religion. The emphasis on inner spirituality, dzikr practice, and end-of-day arrival teaching distinguish this ṭarîqa from mainstream urban religious practices.